Reduction of velocity fluctuation and improvement of performance by undulating in breaststroke - Soons, B.; Colman, V.; Silva, A.; Sanders, R.; Persyn, U. (coachesinfo.com)
This article compares the undulating and flat breaststroke styles of international level men and women. Concepts of propulsion, based on knowledge of motion of marine animals, are explored in the light of statistical evidence.